Lyrical Structuralism in Contemporary Poetry with an Emphasis on the Poem "The Song of Knitting Wool" - Ruhbakhsh Mobasseri, Ali (2020)
The “song of quail” is amongst the impressive poems by the great contemporary poet, Mahdi Akhavan Thaleth; apart from having a dialectal language and containing factional words, the poem presents a marvelous array of senses and lyrical literature. From the linguistic perspectives, “the song of quail” is a vivid sample of the poet’s application of sounds for inducing his affectionate feelings to the readers.In the first step, this study sought showing the lyrical and symbol-generating properties of Akhavan’s poetry (with a particular glance at the song of quail) and capturing the sociopolitical structuralism of the work thereby to arrive at its lyrical structuralism; in the second step, the study tried investigating the poet’s depiction of senses in the poem which is commonly termed the effect of vowels on the meaning. The thing that can be recounted as the present research’s accomplishment is the affectionate feelings’ inducement based on inductive vowels and sociology of the work. Drawn on a free perception of the theory by the French Maurice Grammont and the Russian Roman Jakobson, the present study concluded that the alignment of the vowels with the poem’s significations resulted in the increase in the poetical function and that such an alignment could intensify the meaning and also that the coordination could bar the perception of the meaning if it was not aligned with the words’ denotations.